Anticorrosive grease as well as preparation method and application thereof

By using trimellite and polyαolefin composites as base oils in the anticorrosion and combined with other additives, the existing anticorrosion lacks biodegradability and high and low temperature performance, achieving excellent anticorrosion and environmental protection.

CN120041249AActive Publication Date: 2025-05-27ZHENGZHOU OPTRIS SCI & TECH CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510206109.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-05-27
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

The existing overhead wire anticorrosion lacks biodegradability, high and low temperature properties and oxidative stability, which limits its application.

Method used

Trimellite and polyαolefin compound are used as base oil, and plasticizers, gel agents, anti-rust agents, dispersants, structural stabilizers and antioxidants are added to control the composition and dosage to improve the biodegradability and performance of the anticorrosive.

Benefits of technology

It realizes the biodegradability of anticorrosive liquors, excellent high and low temperature performance, oxidation stability and corrosion resistance, and is suitable for anticorrosion applications of overhead conductors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120041249A_ABST
    Figure CN120041249A_ABST
Patent Text Reader

Abstract

The invention provides preservative grease as well as a preparation method and application thereof, and belongs to the technical field of preservative grease. The trimellitate and the poly-alpha-olefin are compounded to serve as the base oil, the phenomenon that the trimellitate and the plasticizer are not melted after being mixed can be avoided, and meanwhile the biodegradability of the ester oil and the high-temperature stability and excellent low-temperature tendency of the poly-alpha-olefin can be exerted; the antioxidant is added, so that the oxidation resistance of the anti-corrosion grease is improved; the antirust agent is added to improve the antirust performance of the anticorrosive grease; the dispersing agent is added to improve the dispersity of the gel; the composition of the anti-corrosion grease and the dosage of each component are controlled, so that the anti-corrosion grease has certain biodegradability, excellent high and low temperature performance, oxidation stability and anti-corrosion performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of anti-corrosion grease, and particularly relates to an anti-corrosion grease, a preparation method thereof and an application thereof. Background Art

[0002] An overhead conductor is a conductor used for an overhead power transmission line. Since the overhead conductor is exposed to the atmospheric environment for a long time, it will be eroded by substances such as rainwater and salt mist, and usually an anti-corrosion grease is coated to improve the anti-corrosion performance of the overhead conductor. At present, the anti-corrosion grease for overhead conductors is mainly composed of a mineral-based base oil and an anti-corrosion inhibitor, etc., but it is not biodegradable, which will cause harm to the environment. At the same time, its high and low temperature performance and oxidation stability are poor, and the anti-corrosion performance still needs to be further improved, thus limiting its application. Therefore, there is an urgent need for an anti-corrosion grease with biodegradability, excellent high and low temperature performance, oxidation stability and anti-corrosion performance. Summary of the Invention

[0003] The purpose of the present invention is to provide an anti-corrosion grease, a preparation method thereof and an application thereof. The anti-corrosion grease provided by the present invention has certain biodegradability, excellent high and low temperature performance, oxidation stability and anti-corrosion performance.

[0004] In order to achieve the above-mentioned invention purpose, the present invention provides the following technical solutions:

[0005] The present invention provides an anti-corrosion grease, which comprises the following components in parts by mass: 50-85 parts of a base oil, 5-10 parts of a plasticizer, 5-15 parts of a gelling agent, 1-7 parts of a rust inhibitor, 0.5-2 parts of a dispersant, 0.4-1 part of a structure stabilizer and 0.1-1.5 parts of an antioxidant; the base oil comprises trimellitate and polyalphaolefin.

[0006] Preferably, the mass ratio of trimellitate to polyalphaolefin in the base oil is (1-1.5):1.

[0007] Preferably, the plasticizer is a hydrogenated styrene-isoprene copolymer.

[0008] Preferably, the gelling agent is a hydrophobic nano-fumed silica.

[0009] Preferably, the rust inhibitor comprises oxidized wax and oleoyl sarcosine; the mass ratio of oxidized wax to oleoyl sarcosine is 1:(2-5).

[0010] Preferably, the dispersant is n-octyltriethoxysilane.

[0011] Preferably, the structure stabilizer is tert-butyl peroxybenzoate.

[0012] Preferably, the antioxidant includes amine antioxidants and phenolic antioxidants; the mass ratio of the amine antioxidants to the phenolic antioxidants is 1:(1-2).

[0013] The present invention also provides a method for preparing the anti-corrosion grease described in the above technical solution, including the following steps:

[0014] (1) Mix a plasticizer and poly-α-olefin to obtain a mixed solution;

[0015] (2) Mix the mixed solution obtained in step (1) with trimellitate, a gelling agent, a dispersant, a rust inhibitor, a structure stabilizer, and an antioxidant to obtain the anti-corrosion grease.

[0016] The present invention also provides the application of the anti-corrosion grease described in the above technical solution or the anti-corrosion grease prepared by the preparation method described in the above technical solution in the anti-corrosion of overhead conductors.

[0017] The present invention provides an anti-corrosion grease, which includes the following components by mass: 50-85 parts of base oil, 5-10 parts of plasticizer, 5-15 parts of gelling agent, 1-7 parts of rust inhibitor, 0.5-2 parts of dispersant, 0.4-1 part of structure stabilizer, and 0.1-1.5 parts of antioxidant; the base oil includes trimellitate and poly-α-olefin. The present invention combines trimellitate and poly-α-olefin as the base oil, which can avoid the phenomenon of immiscibility after mixing trimellitate and plasticizer, and at the same time can exert the biodegradability of ester oil, the high-temperature stability of poly-α-olefin, and excellent low-temperature tendency; adding an antioxidant improves the antioxidant property of the anti-corrosion grease; adding a rust inhibitor improves the rust prevention performance of the anti-corrosion grease; adding a dispersant improves the dispersibility of the gelling agent; controlling the composition of the anti-corrosion grease and the dosage of each component enables the anti-corrosion grease to have certain biodegradability, excellent high and low temperature performance, oxidation stability, and anti-corrosion performance. The results of the examples show that the anti-corrosion grease provided by the present invention has excellent high-temperature stability and low-temperature adhesion. Description of the Drawings

[0018] Figure 1 It is a high-temperature stability test chart of the anti-corrosion grease in Example 1;

[0019] Figure 2 It is a high-temperature stability test chart of the anti-corrosion grease in Example 2;

[0020] Figure 3 It is a high-temperature stability test chart of the anti-corrosion grease in Example 3;

[0021] Figure 4 It is a high-temperature stability test chart of the anti-corrosion grease in Example 4;

[0022] Figure 5 It is a low-temperature adhesion test chart of the anti-corrosion grease in Example 1;

[0023] Figure 6 It is a test chart of the low-temperature adhesion of the antiseptic grease in Example 2;

[0024] Figure 7 It is a test chart of the low-temperature adhesion of the antiseptic grease in Example 3;

[0025] Figure 8 It is a test chart of the low-temperature adhesion of the antiseptic grease in Example 4;

[0026] Figure 9 It is a test chart of the corrosion test results of the antiseptic grease in Example 1;

[0027] Figure 10 It is a test chart of the corrosion test results of the antiseptic grease in Example 2;

[0028] Figure 11 It is a test chart of the corrosion test results of the antiseptic grease in Example 3;

[0029] Figure 12 It is a test chart of the corrosion test results of the antiseptic grease in Example 4. Detailed implementation mode

[0030] The present invention provides an antiseptic grease, which comprises the following components by mass parts: 50-85 parts of base oil, 5-10 parts of plasticizer, 5-15 parts of gelling agent, 1-7 parts of rust inhibitor, 0.5-2 parts of dispersant, 0.4-1 part of structure stabilizer and 0.1-1.5 parts of antioxidant.

[0031] By mass parts, the antiseptic grease provided by the present invention comprises 50-85 parts of base oil. In the embodiments of the present invention, the dosage of the base oil can be specifically 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts or 85 parts.

[0032] In the present invention, the base oil comprises trimellitate and polyalphaolefin (PAO).

[0033] In the present invention, the mass ratio of trimellitate to polyalphaolefin in the base oil is preferably (1-1.5):1. In the embodiments of the present invention, the mass ratio of trimellitate to polyalphaolefin in the base oil can be specifically 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1. The present invention uses the ester oil and PAO in combination, which can avoid the phenomenon that trimellitate and plasticizer are not compatible, and at the same time can give full play to the biodegradability of the ester oil and the high-temperature stability and excellent low-temperature tendency of PAO. The present invention controls the type and dosage of the base oil within the above range, which can further improve the various performances of the antiseptic grease.

[0034] The present invention has no special limitation on the sources of the trimellitate and polyalphaolefin, and commercially available products well-known to those skilled in the art can be used. In the embodiments of the present invention, the trimellitate is specifically produced by Yingkou Xinghuo Chemical Co., Ltd., with the code TM320B, the kinematic viscosity at 40°C is 320.0 mm 2 / s, the kinematic viscosity at 100°C is 32.0 mm 2 / s, the viscosity index (VI) is 140, the pour point is -35°C, the open flash point is 280°C, and the acid value is 0.05 mg KOH / g; the polyalphaolefin is specifically PAO40 produced by Lanzhou PetroChina Lubricant Additive Co., Ltd., with the kinematic viscosity at 40°C being 407.4 mm 2 / s, the kinematic viscosity at 100°C is 39.84 mm 2 / s, the viscosity index (VI) is 147, the pour point is -36°C, the open flash point is 282°C, the acid value is 0.01 mg KOH / g, and the density (at 20°C) is 0.849 g / cm 3 .

[0035] Based on the mass of the base oil being 50 to 85 parts, the anti-corrosion grease provided by the present invention further includes 5 to 10 parts of a plasticizer. In the embodiments of the present invention, the dosage of the plasticizer can specifically be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, or 10 parts.

[0036] In the present invention, the plasticizer is preferably a hydrogenated styrene-isoprene copolymer. The hydrogenated styrene-isoprene copolymer of the present invention is a linear hydrogenated block copolymer, which consists of a polystyrene segment (hard segment) and a hydrogenated polyconjugated diene segment (soft segment). The polystyrene segment has poor compatibility with most base oils, while the soft segment has good solubility in the base oil. At lower temperatures, this amphiphilic linear VM molecule forms micelles in the oil, thus having good low-temperature performance, and at the same time having good weather and heat resistance. By controlling the type and dosage of the plasticizer within the above range, the present invention can further improve the various properties of the anti-corrosion grease.

[0037] The present invention has no special limitation on the source of the plasticizer, and commercially available products well-known to those skilled in the art can be used. In the embodiments of the present invention, the hydrogenated styrene-isoprene copolymer is specifically M7401 produced by Zhejiang Zhongli Synthetic Materials Technology Co., Ltd., with the mass ratio of styrene / butadiene being 37:63, the specific gravity being 0.91 g / cc, the volatile content being 0.27 wt%, the ash content being 0.1 wt%, and the toluene solution viscosity (at 30°C, 15 wt%) being 720 mPa·S.

[0038] Based on the mass of the base oil being 50 to 85 parts, the anti-corrosion grease provided by the present invention further includes 5 to 15 parts of a gelling agent. In the embodiments of the present invention, the dosage of the gelling agent can specifically be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts.

[0039] In the present invention, the gelling agent is preferably hydrophobic nano-aerosil. In the present invention, the hydrophobic nano-aerosil is modified from hydrophilic fumed silica and has outstanding hydrophobic properties, which can significantly improve the structural stability of the product in a humid environment. By controlling the type and dosage of the gelling agent within the above range, the present invention can further improve the various properties of the anti-corrosion grease.

[0040] The present invention has no special limitation on the source of the gelling agent, and commercially available products well-known to those skilled in the art can be used. In the embodiments of the present invention, the gelling agent is specifically the hydrophobic fumed silica produced by Hubei Huifu Nano Materials Co., Ltd., with the code HB-630, which is a hydrophobic fumed silica after hydrophilic fumed silica is treated with hexamethyldisilazane (HMDS); the loss on drying (dried at 105 °C for 2 h) is 0.3%, the loss on ignition (ignited at 1000 °C for 2 h, based on the product after drying at 105 °C for 2 h) is 2.8%, the silica content (based on the product after ignition) is 99.9 wt%, the carbon content (based on the product after drying at 105 °C for 2 h) is 3.0 wt%, the total specific surface area is 152 m 2 / g, and the median particle size is 10.03 mm.

[0041] Based on the mass of the base oil being 50 to 85 parts, the anti-corrosion grease provided by the present invention further includes 1 to 7 parts of a rust inhibitor. In the embodiments of the present invention, the dosage of the rust inhibitor can specifically be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts or 7 parts.

[0042] In the present invention, the rust inhibitor preferably includes oxidized wax and oleoyl sarcosine. In the present invention, the oxidized wax can form a dense rust-proof film on the surface of the workpiece, and at the same time, compounding with oleoyl sarcosine can more effectively improve its rust-proof performance.

[0043] In the present invention, the mass ratio of the oxidized wax to oleoyl sarcosine is preferably 1:(2 to 5). In the embodiments of the present invention, the mass ratio of the oxidized wax to oleoyl sarcosine can specifically be 1:2, 1:3, 1:4 or 1:5. By controlling the type and dosage of the rust inhibitor within the above range, the present invention can further improve the various properties of the anti-corrosion grease.

[0044] The present invention has no special limitation on the sources of the oxidized wax and oleoyl sarcosine, and commercially available products well-known to those skilled in the art can be used. In the embodiments of the present invention, the oxidized wax is specifically a rust preventive film-forming agent produced by Shanghai Yucheng Chemical Co., Ltd., with the code name RP7031, having a brown solid appearance, an acid value of 31.5 mgKOH / g, and solubility: soluble in mineral oil and solvents; the oleoyl sarcosine is specifically a multi-functional rust preventive agent produced by Shenzhen Ruqinba Chemical Materials Co., Ltd., with the code name AY-Y30, an acid value of 152 mgKOH / g, a pH value of 4, and a density (20 °C) of 0.96 g / cm 3 , belonging to an ashless system.

[0045] Based on 50 to 85 parts by mass of the base oil, the anti-corrosion grease provided by the present invention further includes 0.5 to 2 parts of a dispersant. In the embodiments of the present invention, the dosage of the dispersant can specifically be 0.5 part, 1 part, 1.5 parts or 2 parts.

[0046] In the present invention, the dispersant is preferably n-octyltriethoxysilane. The present invention uses n-octyltriethoxysilane as the dispersant, which has a high flash point and is safe to use compared with traditional dispersants such as ethanol. At the same time, the dosage is small, especially with excellent dispersibility for the gelling agent. The present invention controls the type and dosage of the dispersant within the above range, which can further improve the various performances of the anti-corrosion grease.

[0047] The present invention has no special limitation on the source of the dispersant, and commercially available products well-known to those skilled in the art can be used. In the embodiments of the present invention, the n-octyltriethoxysilane is specifically an organosilane coupling agent produced by Jiangxi Chenguang New Materials Co., Ltd., with the code name CG-801, a molecular weight of 276.49, a specific gravity at 25 °C of 0.879, an open flash point of 100 °C, and a colorless transparent liquid appearance, having outstanding dispersing performance for inorganic thickeners.

[0048] Based on 50 to 85 parts by mass of the base oil, the anti-corrosion grease provided by the present invention further includes 0.4 to 1 part of a structure stabilizer. In the embodiments of the present invention, the dosage of the structure stabilizer can specifically be 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part or 1 part.

[0049] In the present invention, the structure stabilizer is preferably tert-butyl peroxybenzoate. In the present invention, the tert-butyl peroxybenzoate can undergo a curing reaction with the plasticizer hydrogenated styrene-isoprene copolymer at 100 to 140 °C, thereby improving the structural stability of the product at high temperatures. The present invention controls the type and dosage of the structure stabilizer within the above range, which can further improve the various performances of the anti-corrosion grease.

[0050] The present invention has no special limitation on the source of the structural stabilizer, and commercially available products well-known to those skilled in the art can be used. In the embodiments of the present invention, the tert-butyl peroxybenzoate is specifically Trigonox C produced by Nouryon Chemicals Co., Ltd., with a crystallization point of 8 °C and a density (20 °C) of 1.04 g / cm 3 and a kinematic viscosity at 40 °C of 6.523 mm 2 / s.

[0051] Based on 50 to 85 parts by mass of the base oil, the antirust grease provided by the present invention further includes 0.1 to 1.5 parts of an antioxidant. In the embodiments of the present invention, the dosage of the antioxidant can specifically be 0.1 part, 0.3 part, 0.5 part, 0.8 part, 1 part, 1.2 parts or 1.5 parts.

[0052] In the present invention, the antioxidant preferably includes an amine antioxidant and a phenolic antioxidant, and more preferably an amine antioxidant and a high molecular weight phenolic antioxidant. In the present invention, the antioxidant can effectively eliminate free radicals and prevent oxidative degradation, thus having outstanding antioxidant properties in high and low temperature environments and extending the service life of the product.

[0053] In the present invention, the mass ratio of the amine antioxidant to the phenolic antioxidant is preferably 1:(1 - 2). In the embodiments of the present invention, the mass ratio of the amine antioxidant to the phenolic antioxidant can specifically be 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2. By controlling the type and dosage of the antioxidant within the above range, the present invention can further improve the various properties of the antirust grease.

[0054] The present invention has no special limitation on the source of the antioxidant, and commercially available products well-known to those skilled in the art can be used. In the embodiments of the present invention, the antioxidant is specifically liquid nonyl diphenylamine and high molecular weight phenolic antioxidant produced by BASF Chemical Co., Ltd.; the liquid nonyl diphenylamine antioxidant code is L67, with a kinematic viscosity at 40 °C of 675 mm 2 / s and a density (20 °C) of 0.52 g / cm 3 , and the nitrogen content is 3.6 wt%; the high molecular weight phenolic antioxidant code is L107, with a melting point of 50 °C.

[0055] The present invention controls the composition of the antirust grease and the dosage of each component, so that the antirust grease has certain biodegradability, excellent high and low temperature performance, oxidation stability and antirust performance.

[0056] The present invention also provides a preparation method of the antirust grease according to the above technical solution, including the following steps:

[0057] (1) Mix a plasticizer and a poly-α-olefin to obtain a mixed liquid;

[0058] (2) Mix the mixed liquid obtained in the step (1) with a trimellitate, a gelling agent, a dispersant, a rust inhibitor, a structure stabilizer, and an antioxidant to obtain an anti-corrosion grease.

[0059] In the present invention, a plasticizer and a poly-α-olefin are mixed to obtain a mixed liquid.

[0060] In the present invention, the mixing of the plasticizer and the poly-α-olefin is preferably as follows: at room temperature, add the plasticizer to the poly-α-olefin, stir for 20 - 40 min, then heat up to 120 - 130 °C at a heating rate of 60 - 80 °C / min, and keep the temperature at 120 - 130 °C for 50 - 70 min; more preferably: at room temperature, add the plasticizer to the poly-α-olefin, stir for 30 min, then heat up to 120 - 130 °C at a heating rate of 70 °C / min, and keep the temperature at 120 - 130 °C for 60 min.

[0061] After obtaining the mixed liquid, in the present invention, the mixed liquid is mixed with a trimellitate, a gelling agent, a dispersant, a rust inhibitor, a structure stabilizer, and an antioxidant to obtain an anti-corrosion grease.

[0062] In the present invention, the mixing of the mixed liquid with a trimellitate, a gelling agent, a dispersant, a rust inhibitor, a structure stabilizer, and an antioxidant is preferably as follows: add the trimellitate to the mixed liquid at 70 - 90 °C and stir evenly, then successively add the gelling agent and the dispersant, stir at 400 - 500 r / min for 20 - 40 min, perform cyclic shearing at 0.8 - 1.2 MPa for 1 - 2 h, relieve the pressure, add the rust inhibitor, the structure stabilizer, and the antioxidant, perform cyclic stirring for 10 - 30 min, perform cyclic shearing at 0.8 - 1.2 MPa for 20 - 40 min, and relieve the pressure; more preferably: add the trimellitate to the mixed liquid at 80 °C and stir evenly, then successively add the gelling agent and the dispersant, stir at 400 - 500 r / min for 30 min, perform cyclic shearing at 1 MPa for 1.5 h, relieve the pressure, add the rust inhibitor, the structure stabilizer, and the antioxidant, perform cyclic stirring for 20 min, perform cyclic shearing at 1 MPa for 30 min, and relieve the pressure.

[0063] The preparation method of the present invention can make the components mix more evenly.

[0064] The present invention also provides the application of the anti-corrosion grease described in the above technical solution or the anti-corrosion grease prepared by the preparation method described in the above technical solution in the anti-corrosion of overhead conductors.

[0065] The present invention has no special limitation on the operation of the application, and the technical solutions of the application well-known to those skilled in the art can be adopted.

[0066] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0067] Example 1

[0068] An anti-corrosion grease, by mass fraction, consists of the following components: 83.2 parts of base oil (42.2 parts of trimellitate (TM320B), 41.0 parts of poly-α-olefin (PAO 40), and the mass ratio of trimellitate to poly-α-olefin is 1.03:1), 6 parts of plasticizer (hydrogenated styrene-isoprene copolymer M7401), 7 parts of gelling agent (hydrophobic nano-fumed silica HB-630), 2 parts of rust inhibitor (0.5 part of oxidized wax (RP7031), 1.5 parts of oleoyl sarcosine (AY-Y30), and the mass ratio of oxidized wax to oleoyl sarcosine is 1:3), 0.8 part of dispersant (n-octyltriethoxysilane CG-801), 0.5 part of structure stabilizer (tert-butyl peroxybenzoate Trigonox C), and 0.5 part of antioxidant (0.2 part of amine antioxidant (L67), 0.3 part of phenolic antioxidant (L107), and the mass ratio of amine antioxidant to phenolic antioxidant is 1:1.5);

[0069] The preparation method of the anti-corrosion grease is as follows: (1) At room temperature, add the plasticizer to the poly-α-olefin, stir for 30 min, then heat up to 125 °C at a heating rate of 70 °C / min, and keep it at 125 °C for 60 min to obtain a mixed solution;

[0070] (2) Add trimellitate to the mixed solution at 80 °C and stir evenly, then add the gelling agent and dispersant in sequence, stir at 450 r / min for 30 min, perform cyclic shearing at 1 MPa for 1.5 h, relieve pressure, add the rust inhibitor, structure stabilizer, and antioxidant, stir cyclically for 20 min, perform cyclic shearing at 1 MPa for 30 min, relieve pressure, and obtain the anti-corrosion grease.

[0071] Example 2

[0072] An anticorrosive grease, by mass parts, consists of the following components: base oil 78.5 parts (trimellitate (TM320B) 43.0 parts, polyalphaolefin (PAO 40) 35.5 parts, the mass ratio of trimellitate to polyalphaolefin is 1.2:1), plasticizer (hydrogenated styrene-isoprene copolymer M7401) 7 parts, gelling agent (hydrophobic fumed silica HB-630) 9 parts, rust inhibitor 2.8 parts (oxidized wax (RP7031) 0.8 parts, oleoyl sarcosine (AY-Y30) 2 parts, the mass ratio of oxidized wax to oleoyl sarcosine is 1:2.5), dispersant (n-octyltriethoxysilane CG-801) 1.0 part, structure stabilizer (tert-butyl peroxybenzoate Trigonox C) 0.8 part, and antioxidant 0.9 part (amine antioxidant (L67) 0.4 part, phenolic antioxidant (L107) 0.5 part, the mass ratio of amine antioxidant to phenolic antioxidant is 1:1.25);

[0073] The preparation method of the anticorrosive grease is the same as that of Example 1.

[0074] Example 3

[0075] An anticorrosive grease, by mass parts, consists of the following components: base oil 74.9 parts (trimellitate (TM320B) 44.9 parts, polyalphaolefin (PAO 40) 30.0 parts, the mass ratio of trimellitate to polyalphaolefin is 1.5:1), plasticizer (hydrogenated styrene-isoprene copolymer M7401) 8 parts, gelling agent (hydrophobic fumed silica HB-630) 10 parts, rust inhibitor 3.5 parts (oxidized wax (RP7031) 1 part, oleoyl sarcosine (AY-Y30) 2.5 parts, the mass ratio of oxidized wax to oleoyl sarcosine is 1:2.5), dispersant (n-octyltriethoxysilane CG-801) 1.5 parts, structure stabilizer (tert-butyl peroxybenzoate Trigonox C) 1.0 part, and antioxidant 1.1 part (amine antioxidant (L67) 0.5 part, phenolic antioxidant (L107) 0.6 part, the mass ratio of amine antioxidant to phenolic antioxidant is 1:1.2);

[0076] The preparation method of the anticorrosive grease is the same as that of Example 1.

[0077] Example 4

[0078] An anti-corrosion grease, by mass fraction, consists of the following components: base oil 72.1 parts (trimellitate (TM320B) 43.1 parts, polyalphaolefin (PAO 40) 29 parts, and the mass ratio of trimellitate to polyalphaolefin is 1.5:1), plasticizer (hydrogenated styrene-isoprene copolymer M7401) 8 parts, gelling agent (hydrophobic fumed silica HB-630) 11 parts, rust inhibitor 5 parts (oxidized wax (RP7031) 1.5 parts, oleoyl sarcosine (AY-Y30) 3.5 parts, and the mass ratio of oxidized wax to oleoyl sarcosine is 1:2.3), dispersant (n-octyltriethoxysilane CG-801) 1.7 parts, structural stabilizer (tert-butyl peroxybenzoate Trigonox C) 1.0 part, and antioxidant 1.2 parts (amine antioxidant (L67) 0.5 part, phenolic antioxidant (L107) 0.7 part, and the mass ratio of amine antioxidant to phenolic antioxidant is 1:1.4);

[0079] The preparation method of the anti-corrosion grease is the same as that in Example 1.

[0080] Test the penetration, dropping point, short-term high-temperature stability, low-temperature adhesiveness, and acid value / alkali value of the anti-corrosion greases in Examples 1 to 4. The test method for penetration is GB / T 362925.5.2, the test method for dropping point is GB / T 362925.3, the test method for short-term high-temperature stability is GB / T 362925.4, the test method for low-temperature adhesiveness is GB / T 362925.6, and the test method for acid value / alkali value is GB / T 362925.7. The results are shown in Table 1. Table 1 Penetration, dropping point, short-term high-temperature stability, low-temperature adhesiveness, and acid value / alkali value of the anti-corrosion greases in Examples 1 to 4

[0081]

[0082]

[0083] The test charts of the high-temperature stability (24 h) of the anti-corrosion greases in Examples 1 to 4 are respectively as Figures 1 to 4 shown, and the test charts of the low-temperature adhesiveness (1 h) are respectively as Figures 5 to 8 shown. From the data in Table 1 and Figures 1 to 8 it can be seen that Examples 1 to 4 can all meet the design indicators, and the high-temperature stability of Example 3 is particularly prominent. The addition of plasticizer and gelling agent will make the penetration smaller, while the increase in the addition of rust inhibitor will make the penetration larger. At the same time, the control of penetration has a greater impact on high-temperature stability, and the content of plasticizer also has a certain impact on the high-temperature stability of the product.

[0084] The anti-corrosion grease of Examples 1 to 4 was subjected to aging corrosion tests according to GB / T 362925.8 and GB / T 362925.9. The corrosion test levels, the change rate of penetration during the aging test, and the acid value / alkali value after the aging test are shown in Table 2.

[0085] Table 2 Corrosion test levels, change rate of penetration during the aging test, and acid value / alkali value after the aging test of the anti-corrosion grease of Examples 1 to 4

[0086]

[0087] The corrosion test results of the anti-corrosion grease of Examples 1 to 4 are respectively as Figures 9 to 12 . From the data in Table 2 and Figures 9 to 12 it can be seen that Examples 1 to 4 can all meet the aging corrosion index. The corrosion test performances of Examples 3 and 4 are particularly prominent.

[0088] The biodegradability of the anti-corrosion grease of Examples 1 to 4 was tested, and the results are shown in Table 3.

[0089] Table 3 Biodegradability of the anti-corrosion grease of Examples 1 to 4

[0090] Biodegradation rate % Example 1 62 Example 2 58 Example 3 63 Example 4 59

[0091] From Table 3, it can be seen that compared with the biodegradation rate of traditional mineral-type anti-corrosion grease for overhead conductors (generally 20 - 40%), the biodegradation rate of the anti-corrosion grease of the present invention is at a relatively high level and belongs to a relatively easily degradable product. The biodegradability of the product has a great relationship with the base oil and is also affected by the gelling agent and the rust inhibitor. The anti-corrosion is affected by high temperature. When selecting the gelling agent, silica with better high-temperature performance needs to be selected, but silica has a certain adverse effect on biodegradability. When selecting the rust inhibitor, a non-ash system is more conducive to improving biodegradability.

[0092] In summary, the anti-corrosion grease provided by the present invention has excellent high and low temperature performance, anti-corrosion performance, and good biodegradability.

[0093] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.

Claims

1. A corrosion-resistant grease, comprising the following components by mass: 50-85 parts of base oil, 5-10 parts of plasticizer, 5-15 parts of gelling agent, 1-7 parts of rust inhibitor, 0.5-2 parts of dispersant, 0.4-1 parts of structural stabilizer and 0.1-1.5 parts of antioxidant; the base oil comprises trimellitic acid ester and poly-alpha-olefin.

2. The antiseptic fat according to claim 1, characterized in that The mass ratio of trimellitic acid ester to poly-alpha-olefin in the base oil is (1-1.5):

1.

3. The antiseptic fat according to claim 1, characterized in that: The plasticizer is hydrogenated styrene isoprene copolymer.

4. The antiseptic fat according to claim 1, characterized in that: The gelling agent is hydrophobic nanometer fumed silica.

5. The antiseptic fat according to claim 1, characterized in that: The rust inhibitor comprises oxidized wax and oleoyl sarcosine; the mass ratio of the oxidized wax to oleoyl sarcosine is 1:(2-5).

6. The antiseptic fat according to claim 1, characterized in that: The dispersant is n-octyltriethoxysilane.

7. The antiseptic fat according to claim 1, characterized in that: The structural stabilizer is tert-butyl peroxybenzoate.

8. The antiseptic fat according to claim 1, characterized in that: The antioxidants include amine antioxidants and phenolic antioxidants; the mass ratio of the amine antioxidants to the phenolic antioxidants is 1:(1-2).

9. The method for preparing the preservative fat according to any one of claims 1 to 8, comprising the following steps: (1) mixing a plasticizer and a poly-alpha olefin to obtain a mixed solution; (2) The mixed solution obtained in step (1) is mixed with trimellitic acid ester, gelling agent, dispersant, rust inhibitor, structural stabilizer and antioxidant to obtain antiseptic fat.

10. Use of the anti-corrosion grease according to any one of claims 1 to 8 or the anti-corrosion grease prepared by the preparation method according to claim 9 in the anti-corrosion of overhead wires.

Citation Information

Patent Citations

  • Heat-conducting lubricating grease and preparation method and application thereof

    CN111534358A

  • Flame-retardant water-blocking paste for environment-friendly communication optical cable and preparation method of flame-retardant water-blocking paste

    CN113403126A

  • Environment-friendly anti-corrosion grease for overhead wire and preparation method of environment-friendly anti-corrosion grease

    CN113403127A

  • Lubricating grease for harmonic reducer and preparation method thereof

    CN115786018A

  • Lubricating grease as well as preparation method and application thereof

    CN115838612A